Report of the Managing Director to the International Monetary and Financial Committee on the IMF's Policy Agenda. (Policy Papers; Policy Paper ;, 2006)
This report provides an update of the work and direction of the Fund since the 2005 Annual Meetings. Over the past six months, a principal area of work has been the development of concrete proposals for the implementation of the Managing Director's Report on the Fund's Medium-Term Strategy, endorsed by the IMFC last September.